2020
DOI: 10.3390/nu12061622
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Short-Term Isoflavone Intervention in Polycystic Ovary Syndrome (PCOS) Patients on Microbiota Composition and Metagenomics

Abstract: Background: Polycystic ovary syndrome (PCOS) affects 5–20% of women of reproductive age worldwide and is associated with disorders of glucose metabolism. Hormone and metabolic signaling may be influenced by phytoestrogens, such as isoflavones. Their endocrine effects may modify symptom penetrance in PCOS. Equol is one of the most active isoflavone metabolites, produced by intestinal bacteria, and acts as a selective estrogen receptor modulator. Method: In this interventional study of clinical and biochemical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 136 publications
0
27
0
Order By: Relevance
“…Using 16S rRNA gene sequencing, multiple studies reported that beta diversity was altered in fecal samples obtained from women with PCOS compared with healthy women [ 19 , 22 , 28 ]. However, in other studies, no significant difference in beta diversity was detected in women with PCOS compared with healthy women [ 21 , 26 , 33 , 34 ], potentially due to small sample sizes. Comparing adolescent girls with PCOS and obesity to BMI-matched controls, changes in beta diversity were also observed between the 2 groups [ 37 ].…”
Section: Dysbiosis Of the Gut Microbiome Is Associated With Polycystimentioning
confidence: 77%
See 3 more Smart Citations
“…Using 16S rRNA gene sequencing, multiple studies reported that beta diversity was altered in fecal samples obtained from women with PCOS compared with healthy women [ 19 , 22 , 28 ]. However, in other studies, no significant difference in beta diversity was detected in women with PCOS compared with healthy women [ 21 , 26 , 33 , 34 ], potentially due to small sample sizes. Comparing adolescent girls with PCOS and obesity to BMI-matched controls, changes in beta diversity were also observed between the 2 groups [ 37 ].…”
Section: Dysbiosis Of the Gut Microbiome Is Associated With Polycystimentioning
confidence: 77%
“…Recent studies have shown that alpha diversity of gut microbiota is altered in women with PCOS compared with healthy women. By sampling the fecal microbial content and sequencing 16S ribosomal RNA (rRNA) genes amplified with universal bacterial primers, multiple studies demonstrated that alpha diversity of gut bacteria decreased in premenopausal women with PCOS as compared with age-matched, healthy women [ 19 , 22 , 26–28 , 33 ]. In contrast, 3 studies did not observe significant changes in alpha diversity between women with PCOS and healthy women, potentially due to small sample sizes [ 21 , 24 , 34 ].…”
Section: Dysbiosis Of the Gut Microbiome Is Associated With Polycystimentioning
confidence: 99%
See 2 more Smart Citations
“…For example, after isoflavone intervention, a 50 mg isoflavones/day regimen over just three consecutive days improved predicted stool metagenomic pathways, microbial alpha diversity, and glucose homeostasis in PCOS patients. The effect was so profound that, post-treatment, these variables resembled the profile of the control group at baseline [ 182 ]. Though further testing is required, evidence suggests that dietary supplementation of genistein may be a viable natural option for treating many of the symptoms of PCOS [ 175 , 176 , 177 , 178 , 179 ].…”
Section: Genistein and Women’s Diseasesmentioning
confidence: 99%